Ethical Framework Penggunaan AI dalam Metodologi Penelitian: Tantangan dan Solusi Kontemporer - Eriana, Emi Sita; Oka Safitri, Galuh (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
Artificial intelligence (AI) has transformed scientific research but faces significant ethical challenges in its implementation. This study develops a comprehensive ethical framework for the use of AI in research methodology through mixed-method sequential explanatory design. The survey was conducted on 400 researchers at Indonesian and ASEAN higher education institutions, complemented by in-depth interviews with 30 informants. Quantitative data were analyzed using SPSS and qualitative data using NVivo, reinforced by systematic literature review and document analysis for triangulation. The results revealed three main themes: 78% of researchers do not fully understand the AI algorithms used, the conflict between efficiency and traditional ethical standards, and the urgent need for specific AI ethics guidance. The findings show 73% of researchers are aware of the importance of AI ethics yet only 31% implement it consistently, with 89% requiring training and 67% reporting inadequate institutional support. The research successfully develops an ethical framework with five pillars: Transparency and Accountability, Privacy and Data Protection, Bias Mitigation and Fairness, Human Oversight and Control, and Continuous Monitoring and Evaluation, which provides practical guidance and policy blueprints for ethical and responsible AI adoption in the global academic community.